Case Report: Chemotherapy-Associated Systemic Sclerosis: Is DNA Damage to Blame? - Du, Amy X.; Gniadecki, Robert; Storek, Jan; Osman, Mohamed (Frontiers in Medicine, 2022)
Systemic sclerosis, also known as scleroderma, is an autoimmune disease characterized by cutaneous and visceral fibrosis, immune dysregulation, and vasculopathy. Generally, the degree of skin fibrosis is associated with an increased likelihood of visceral organ involvement. Its pathogenesis is poorly understood; however, it is clear that changes in both the innate and adaptive immune responses are associated with fibroblast dysfunction and vascular damage. Further, DNA damage has been postulated as one of the triggering factors in systemic sclerosis, although the association of DNA damage with the progression of this disease is more poorly established. Recently, abnormal DNA damage response repair pathways have also been identified in patients with systemic sclerosis, suggesting that cells from patients with this disease may be more susceptible to DNA damaging agents. Chemotherapeutic drugs and other DNA damaging agents have been associated with the development of systemic sclerosis, as these agents may provide additional “hits” that promote abnormal DNA damage responses and subsequent inflammatory changes. Herein, we present the case of a 39-year-old female who developed scleroderma after the treatment of her breast cancer with chemotherapeutic agents. Her scleroderma was subsequently successfully treated with autologous hematopoietic stem cell transplantation. We also completed a literature review for previously published cases of chemotherapy associated with systemic sclerosis and highlighted a role of DNA damage in promoting the disease. Our case is the first case of chemotherapy associated with systemic sclerosis treated with hematopoietic stem cell transplantation.